Examining the Relationship Between Teachers' Qualifications and Students' Academic Performance - Tugume, Geoffrey; Silaji, Turyamureeba; Eze, Chidinma Esther; Eze, Val Hyginus Udoka (Journal of Humanities and Social Sciences (JHASS), 2024)
This study delves into the intricate relationship between teacher professionalism, adherence to the code of conduct, commitment, and their overall performance in both classroom settings and extracurricular activities. The findings reveal a clear and significant correlation between high levels of professionalism and strict adherence to the code of conduct with exceptional performance in various teaching duties. This suggests that teachers who uphold these standards are more likely to excel in their roles. Interestingly, the study uncovers an unexpected result: there is no significant relationship between teacher commitment and their performance outcomes. This discrepancy challenges conventional expectations, indicating that commitment alone may not directly influence performance levels. Despite this, the research underscores the profound impact that teachers' attitudes—whether positive or negative—have on their overall effectiveness and performance. A noteworthy observation from the study is the positive attitude of a substantial number of participants towards the teacher code of conduct. This positive disposition towards the code is likely to contribute to enhancing performance and upholding professional standards. Overall, the study highlights the crucial role of professionalism and adherence to conduct in achieving high performance, while also recognizing the need for a broader understanding of how commitment and attitude interplay in educational settings.